Licopeno diminui a lesão cerebral isquêmica por inibição da inflamação em camundongos - Neves, Julliana Catharina de Sousa (2017)
Ischemic cerebrovascular accident results from reduced blood supply to brain tissue, resulting in deprivation of glucose and oxygen characterized by rapid loss of neurological function. Stroke it’s the second leading cause of death and the first cause of disability worldwide. Lycopene is a member of the carotenoid family of phytochemicals and has been demonstrated to be effective in anti-oxidative stress, anti-inflammatory and antiapoptotic reaction in the models of neurodegenerative diseases. The aim of this work was study the effect of lycopene in the neuronal damage, memory deficits and neuroinflammatory response in mice subjected to experimental model of focal cerebral brain ischemia by occlusion of middle cerebral artery (pMCAO). One hundred and fifty-six animals were divided into 7 groups as following: 1. sham-operated, 2. sham-operated treated with lycopene (20 mg/kg v.o.), 3. ischemic animals (pMCAO), 4. ischemic animals treated with lycopene at 2 mg/kg p.o., 5. ischemic animals treated with lycopene at 10 mg/kg p.o., 6. ischemic animals treated with lycopene at 20 mg/kg 7 ischemic animals treated with lycopene at 40 mg/kg p.o. Lycopene treatment were initiated 2 h after pMCAO induction once a day in 4 days following. The effect on ischemic damage was assessed by TTC staining and sensorimotor damage through the neurological evaluation scale. Lycopene decreased the area of ischemic infarction and improved the sensory-motor performance of the animals at 20 mg/kg. The locomotor activity was evaluated through the open field test. The ischemic animals presented increased number of crossings and decreased number of rearings and lycopene reversed these changes at 20 mg/kg. The pMCAO produced deficits in operational memory, episodic memory, spatial memory and aversive memory and the treatment with lycopene (20 mg/kg) prevented memory deficits. The role of neuroinflammation was assessed through the evaluation of astrogliosis (GFAP) and the expression of TNF-α and NF-κB. The action of lycopene on synaptogenesis and GSK-3B expression was also evaluated. Lycopene decreased inflammation by decreasing GFAP in the cortex, TNF-α and NF-κB in the cortex and striatum and has no effect on synaptogenesis. The results of this study suggest that lycopene has neuroprotective activity probably due to its effect against neuroinflammation. Our study provides experimental evidence for using lycopenein the treatment of cerebral ischemia.